2020
DOI: 10.3389/fcell.2020.00373
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Requirement for the GINS Complex During Zebrafish Development

Abstract: Efficient and accurate DNA replication is particularly critical in stem and progenitor cells for successful proliferation and survival. The replisome, an amalgam of protein complexes, is responsible for binding potential origins of replication, unwinding the double helix, and then synthesizing complimentary strands of DNA. According to current models, the initial steps of DNA unwinding and opening are facilitated by the CMG complex, which is composed of a GINS heterotetramer that connects Cdc45 with the mini-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Together, these findings suggest that in the context of asymmetric cell division, CMG has a conserved role in the divergence of cell fates that is distinct from its conserved role in DNA unwinding. Finally, the idea that CMG has a conserved role in cell fate is supported by previous observations implicating Psf2 GINS2 in nervous system development in Xenopus and zebrafish 51,52 , Sld5 GINS4 in early embryonic development and nervous system development in mouse 53,54 and MCM5 in neuronal differentiation in Drosophila 55 .…”
Section: Discussionmentioning
confidence: 60%
“…Together, these findings suggest that in the context of asymmetric cell division, CMG has a conserved role in the divergence of cell fates that is distinct from its conserved role in DNA unwinding. Finally, the idea that CMG has a conserved role in cell fate is supported by previous observations implicating Psf2 GINS2 in nervous system development in Xenopus and zebrafish 51,52 , Sld5 GINS4 in early embryonic development and nervous system development in mouse 53,54 and MCM5 in neuronal differentiation in Drosophila 55 .…”
Section: Discussionmentioning
confidence: 60%
“…From an oncological view, aberrant high expression of PAX5 and GINS1 blocked B-cell differentiation. In addition, GINS1 recently was reported to have anti-apoptotic functions, 48,49 all these findings sug-…”
Section: Discussionmentioning
confidence: 92%
“…From an oncological view, aberrant high expression of PAX5 and GINS1 blocked B‐cell differentiation. In addition, GINS1 recently was reported to have anti‐apoptotic functions, 48,49 all these findings suggested that deregulated PAX5 and GINS1 are an oncogene for a fraction of DLBCL. Furthermore more cell lines, more tissue samples and further studies are needed to establish the therapeutic potential of GINS1 in DLBCL.…”
Section: Discussionmentioning
confidence: 97%
“…This is critical in ensuring that newly formed cells have accurate genetic information after each cell division [ 27 ]. GINS1’s expression is related to different stages of the cell cycle, especially during the S phase (DNA replication) and M phase (mitosis), where it plays an essential role in aiding DNA replication and ensuring proper chromosome separation [ 28 ]. Dysfunctional GINS1 may lead to DNA replication errors, chromosome instability, and cell cycle issues, highly relevant to various diseases, including cancer.…”
Section: Discussionmentioning
confidence: 99%